2019
DOI: 10.1111/1756-185x.13514
|View full text |Cite
|
Sign up to set email alerts
|

Treat‐to‐target in rheumatoid arthritis: Evaluating the patient perspective using the Patient Opinion Real‐Time Anonymous Liaison system: The RA T2T PORTAL study

Abstract: Objectives:To determine the level of agreement among patients with rheumatoid arthritis (RA) with the principles and recommendations of the treat-to-target (T2T) initiative in New Zealand (NZ) and to further explore specific patient opinions via online iterative surveys. Methods: Participants with RA were recruited from rheumatology clinics in NZ and invited to receive and reply to surveys administered via the Patient Opinion Real-Time Anonymous Liaison (PORTAL) system. An enrolment survey recorded demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…Currently, the core principles of the treat-to-target (T2T) strategy in RA are shared decision-making and regular patient review with a target of REM or, failing that, low disease activity to ensure optimal outcomes (37,38). Therefore, objective parameters of REM are necessary to achieve a successful outcome following the T2T strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the core principles of the treat-to-target (T2T) strategy in RA are shared decision-making and regular patient review with a target of REM or, failing that, low disease activity to ensure optimal outcomes (37,38). Therefore, objective parameters of REM are necessary to achieve a successful outcome following the T2T strategy.…”
Section: Discussionmentioning
confidence: 99%
“…17 Additionally in 2 further studies from Canada and New Zealand which sought patient perspectives on RA-T2T, both demonstrated high levels of agreement with the principles and recommendations. 21,22 Rheumatologists in this survey agreed highly with RA-T2T recommendations with the exception of the routine use of a validated composite disease activity score. Forty-nine percent of rheumatologists reported they always or very often used a disease activity score in daily practice to guide treatment decisions.…”
Section: Discussionmentioning
confidence: 64%
“…This is supported by a previous report indicating that a patient version of the original RA‐T2T principles and recommendations was endorsed with high levels of agreement by patients 17 . Additionally in 2 further studies from Canada and New Zealand which sought patient perspectives on RA‐T2T, both demonstrated high levels of agreement with the principles and recommendations 21,22 …”
Section: Discussionmentioning
confidence: 93%
“…Patients with rheumatoid arthritis (RA) included in this study were enrolled from a group of patients who had volunteered to offer ongoing opinions on their experience of living with RA via an online sampling project, The Patient Opinion Real‐Time Anonymous Liaison project (30). Patients with ankylosing spondylitis (AS) were recruited during 2018 by a research assistant through the Dunedin Hospital Rheumatology Outpatients Clinic and from a database of patients who participated in the Spondyloarthritis Genetics and the Environment study, a 5‐year longitudinal study looking at outcomes in spondyloarthritis.…”
Section: Methodsmentioning
confidence: 99%